Why antislavery poetry matters now - Yothers, Brian, 1975- (Studies in American literature and culture., 2023)
"The poetry of the transatlantic abolitionist movement represented a powerful alliance across racial and religious boundaries; today it challenges the demarcation in literary studies between cultural and aesthetic approaches. Now is a particularly apt moment for its study. This book is a history of the nineteenth-century poetry of slavery and freedom framed as an argument about the nature of poetry itself: why we write it, why we read it, how it interacts with history. Poetry that speaks to a broad cross-section of society with moral authority, intellectual ambition, and artistic complexity mattered in the fraught years of the mid nineteenth century; Brian Yothers argues that it can and must matter today. Yothers historicizes the poetry he examines in light of recent work by historians, scholars in literary, cultural, and rhetorical studies, political scientists, sociologists, African-Americanists, scholars of race and gender studies, and theorists of poetics. That interdisciplinary sweep is mirrored by the range of writers he considers: from the canonical--Whitman, Barrett Browning, Beecher Stowe, DuBois, Melville--to those whose influence has faded--Longfellow, Lydia Huntley Sigourney, John Pierpont, John Greenleaf Whittier, Thomas Wentworth Higginson, James Russell Lowell--to African American writers whose work has been recently rediscovered--James M. Whitfield, William Wells Brown, George Moses Horton, Frances E.W. Harper"--